Young People, Being Catholic, and Religious Change in the Philippines: A Response to Critics - Cornelio, Jayeel (Archīum Ateneo, 2018)
This article is a response to the comments offered by Giovanni Maltese, Peter Bräunlein, Rosa Cordillera A. Castillo, and Scott MacLochlainn on the book Being Catholic in the Contemporary Philippines: Young People Reinterpreting Religion. It addresses several areas including the limits and potential of conducting research on religious identity and the book’s arguments about reflexive spirituality and individualization. It ends by reflecting on the urgency of assessing religious change in the Philippines, which involves diversification and the rise of militant Christianity.